A mitochondria targetable near-infrared fluorescence probe for glutathione visual biological detection. Issue 5 (20th January 2022) - Jia, Mingxuan; Wei, Liangnian; Lu, Yuxun; Zhang, Ruqiu; Chen, Qiuling; Xia, Wenjiang; Liu, Ye; Li, Fan; Zhou, Ying
Abstract : A mitochondria targetable fluorescence probe with 730 nm emission was developed for GSH detection. The probe successfully imaged GSH in HeLa cells and C. elegans, and was applied in rat brain slices imaging. Abstract : Glutathione (GSH), an abundant non-protein thiol, plays a crucial role in numerous biotic processes. Herein, a mitochondria-targeted near-infrared GSH probe (JGP ) was synthesized, which displayed desired properties with high specificity and sensitivity, appreciable water solubility, and rapid response time. In the presence of GSH, nearly a 13-fold fluorescence emission growth appeared at 730 nm and the solvent color changed from blue to cyan. The sensing mechanism of JGP and GSH was confirmed by a high-resolution mass spectroscopy analysis. Moreover, good cell penetration enabled JGP to be successfully used for imaging biological samples such as HeLa cells, C. elegans, and especially rat brain slices. Imaging experiments showed that JGP could monitor the GSH concentration changes with a dose-dependent direct ratio in all the tested samples. The successful application of JGP in brain imaging indicates that JGP is a suitable GSH optical probe, which may have wide application value in fields of brain imaging. It also lays a theoretical and practical foundation for the further application of fluorescent probes in brain sciences.